2018
DOI: 10.1007/s00520-018-4426-4
|View full text |Cite
|
Sign up to set email alerts
|

Unmet supportive care needs in Hispanic/Latino cancer survivors: prevalence and associations with patient-provider communication, satisfaction with cancer care, and symptom burden

Abstract: Findings document unmet supportive care needs in Hispanic/Latino cancer survivors and suggest that reducing unmet needs in Hispanic/Latino cancer survivors may improve not only satisfaction with care, but also health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 44 publications
4
44
1
Order By: Relevance
“…The pattern of results is similar to those of a previous study that found that colorectal cancer survivors undergoing primary cancer treatment and randomized to PN demonstrated greater HRQOL (specifically emotional well‐being) than controls but found no effect of PN on HRQOL among breast cancer survivors undergoing primary cancer treatment. Previous research has also demonstrated that Latina breast cancer survivors after primary treatment completion specifically report greater unmet supportive care needs and lower HRQOL and self‐efficacy in comparison with both Latino prostate and colorectal survivors …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The pattern of results is similar to those of a previous study that found that colorectal cancer survivors undergoing primary cancer treatment and randomized to PN demonstrated greater HRQOL (specifically emotional well‐being) than controls but found no effect of PN on HRQOL among breast cancer survivors undergoing primary cancer treatment. Previous research has also demonstrated that Latina breast cancer survivors after primary treatment completion specifically report greater unmet supportive care needs and lower HRQOL and self‐efficacy in comparison with both Latino prostate and colorectal survivors …”
Section: Discussionmentioning
confidence: 98%
“…Previous research has also demonstrated that Latina breast cancer survivors after primary treatment completion specifically report greater unmet supportive care needs and lower HRQOL and self-efficacy in comparison with both Latino prostate and colorectal survivors. 63,64 Therefore, because of their vulnerability in comparison with not only NLWs but also Latino survivors diagnosed with the 2 other common cancers, it is crucial that future research be focused on specifically identifying efficacious interventions that improve HRQOL among both Latina breast cancer survivors and Latino prostate cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Rural cancer survivors experience a greater need for physical and daily living care needs that may be associated with limited access to resources. 34 Adequate review and delivery of care needs can improve a survivor's quality of life, 3,35 satisfaction of care, 3 follow-up care initiation and adherence, and other related survivorship outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…2 In addition to advancements in cancer treatments, effective patient-provider communication is a major facilitator for optimizing survivorship outcomes. [3][4][5] Communication including, but not limited to, a treatment summary, information on the possible late-term effects of treatment, recommended follow-up screenings to monitor recurrent cancers, and a communication plan between health care providers show promise of improving a patient's understanding of their survivorship care and the potential to improve patientreported survivorship outcomes. 4,5 Consequentially, a poor understanding of the utility of posttreatment survivorship care can be a barrier to adequate survivorship care, as patients may delay the initiation of or reduce adherence to follow-up care screening for recurrent cancers, lack knowledge of the long-term effects of treatment, and have unaddressed psychosocial (ie, emotional and social) supportive care needs.…”
mentioning
confidence: 99%
“…Though Latino/as have lower incidence and death rates for common cancers than non‐Hispanic whites, they have poorer access to and less utilization of health care relative to other racial/ethnic groups, and are less likely to be diagnosed with localized cancer . Latino/as with cancer report lower quality of life (QOL) and experience a higher number of informational and supportive care needs as compared with African‐American and non‐Hispanic whites with cancer. As such, Latino/a cancer survivors may experience different supportive care needs than other populations.…”
Section: Introductionmentioning
confidence: 99%